A Very Rare Case Report of Sigmoid Adenocarcinoma with Involvement of the Bladder at the time of initial diagnosis - Hadian, Babak; Khodadadi, Babak; Rezaei, Nahid; Ghanadi, Kourosh (Bangladesh Journal of Medical Science, 2019)
In nephro-urologic field, extent of approach to causes of lower urinary tract complaints in fourth decade or more of life is challenging matter. Physicians must notice to alarm signs in diagnosis of patients to prevent misdiagnosis of important causes. in practice, combination of hematuria and constipation accompany weight loss are red flags. Bladder neoplasm is a malignant cause of above symptoms that sometime originate from neighboring organ. Bladder metastases are very rare in colorectal cancers (CRC). Symptoms of primary tumor may be precede or coincide with urinary symptoms. The present study describes an unusual case of symptomatic bladder involvement from sigmoid adenocarcinoma. A 68-year-old man with complaints of dysuria, frequency, microscopic-hematuria, nausea, vomiting, and abdominal pain was diagnosed as adenocarcinoma of sigmoid colon metastatic to the bladder. This case underlined the need to prompt and careful attention to patients with hematuria-dysuria in adult age. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.827-829